2016
DOI: 10.1016/j.geb.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Price competition and reputation in credence goods markets: Experimental evidence

Abstract: In credence goods markets, experts have better information about the appropriate quality of treatment than their customers. Because experts provide both the diagnosis and the treatment, there is opportunity for fraud. We experimentally investigate how the intensity of price competition and the level of customer information about past expert behavior inuence experts' incentives to defraud their customers when experts can build up reputation. We show that the level of fraud is signicantly higher under price comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Although only ~20% of prices were equal markup, physicians still provided over 50% honest treatment in most sessions. This propensity for honesty was also documented in the literature ( 11 , 15 , 17 ). Overtreat (undertreat) pricing was closely related to the overtreatment (undertreatment) behavior of physicians.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Although only ~20% of prices were equal markup, physicians still provided over 50% honest treatment in most sessions. This propensity for honesty was also documented in the literature ( 11 , 15 , 17 ). Overtreat (undertreat) pricing was closely related to the overtreatment (undertreatment) behavior of physicians.…”
Section: Resultssupporting
confidence: 67%
“…In recent years, the adoption of experimental methodologies has supplied vital empirical evidence and bolstered the promotion of the field. Only Dulleck et al ( 11 ) and Mimra et al ( 15 ) examined the role of competition through experiments and both found that price competition lowers the market price but leads to an increase in fraud by sellers. Dulleck et al ( 11 ) and Mimra et al ( 15 ) assumed that all experts and consumers are homogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of many other institutions-such as competition, reputation, second opinions, price regulation, reduction in insurance coverage, and media-have been investigated to improve market outcomes (see, e.g., Balafoutas, Beck, Kerschbamer, & Sutter, 2013;Balafoutas, Kerschbamer, & Sutter, 2017;Dulleck et al, 2011;Huck, Lünser, Spitzer, & Tyran, 2016;Kerschbamer, Neururer, & Sutter, 2016, 2019Liu, Brynjolfsson, & Dowlatabadi, 2019;Mimra, Rasch, & Waibel, 2016a, 2016bRajgopal & White, 2019;Rasch & Waibel, 2018). In sum, this literature suggests that, theoretically, several institutions should be able to mitigate market inefficiencies in the credence goods market.…”
mentioning
confidence: 99%
“… Other experimental studies include Kerschbamer, Neururer and Sutter () and Mimra, Rasch and Waibel () (see Kerschbamer and Sutter, for an overview). …”
mentioning
confidence: 99%